2012
DOI: 10.3746/jkfn.2012.41.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physicochemical Properties of Haetsun Vegetables by Blanching

Abstract: This study was conducted to investigate the physicochemical properties of raw and blanched Haetsun vegetables.The proximate composition, reducing sugar, free amino acid, organic acid, vitamin C and mineral composition were compared between raw and blanched Haetsun vegetables. After blanching treatment, the moisture content of Haetsun vegetables was increased, but the crude ash, crude fat, crude fiber, and crude protein content decreased in all samples. C. sinensis contained the highest level of reducing sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…The quality of the meat mostly depends on the color, tenderness, and flavor. Many studies have reported the quality of cooked meat following heat treatment in terms of flavor, color, and hardness ( Kim et al ., 2012 ; Mancini and Hunt, 2005 ; Tornberg, 2005 ; Vasanthi et al ., 2007 ). Thermal treatment of HMR products is the most important process for determining the final quality of the product and its shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the meat mostly depends on the color, tenderness, and flavor. Many studies have reported the quality of cooked meat following heat treatment in terms of flavor, color, and hardness ( Kim et al ., 2012 ; Mancini and Hunt, 2005 ; Tornberg, 2005 ; Vasanthi et al ., 2007 ). Thermal treatment of HMR products is the most important process for determining the final quality of the product and its shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the exposure of chronic stress caused depletion of monoamine hormones; however, EFCS increased the levels of dopamine, tryptophan, 5-HT, and melatonin ( Figure 6 ). It has been reported that Cedrela sinensis leaf is rich in hormonal precursor amino acids, such as tryptophan, tyrosine, and glutamic acid, that are associated with stress reduction [ 74 , 75 ]. These amino acids are absorbed into the body and converted to serotonin, melatonin, dopamine, and γ-aminobutyric acid (GABA), and they suppress stress and help to suppress the imbalance of the HPA axis [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…본 연구결과에 따르면 대부분의 국내 다소비 채소류에서 데침 처리 시 원재료 대비 비타민 B5 및 B6의 함량이 감소하였으며, 이는 Selman(1993)의 보고와 같이 데치는 과정에서 수용성 비타민이 일부 조리수로 용출되고 열에 의해 파괴되었기 때문인 것 으로 판단된다. 역시 열에 민감한 수용성 비타민 성분은 식품의 데침 처리 시 가열에 의한 조직 파괴와 연화에 의해 조리수로 수용성 비타민 성분이 용출 되므로 수용성 비타민 함량이 감소한 것으로 판단된다고 보고한 바 있으며, Kim et al(2012)은 당근, Hwang et al(2012)은 고추를 재료로 사용하여 비타민 C의 함량을 분석한 결과, 데침 처리 시 원재료 대비 비 타민 C의 함량 감소폭이 크고 조리시간이 길어질수록 크게 감소한다고 보고하였다.…”
Section: 채소류 중 비타민 B5 및 B6 함량 평가unclassified